Consumer And Commercial Practices in International Business from An Economic Perspective - Nurul Syafiqah Azman; Nasib Nasib; Affendy Abu Hassim; Said Nasser Al-Amrani; Muhammad Fathoni (Yayasan Bina Bisnis Nusantara Medan, 2026)
The intersection of consumer behaviour and commercial practices in international business contexts represents a critical area of economic research. As international ties become more robust, the awareness of the economic effects stemming from multinational cooperation between organizations and their clientele is elevating. This systematic literature review seeks to amalgamate contemporary scholarship on consumer and commercial practices within the realm of international business from an economic standpoint, with the aim of elucidating critical themes, theoretical frameworks, methodological approaches, and existing research deficiencies. A comprehensive search was conducted across main databases including Scopus and Pro Quest. The primary emphasis of the search strategy was on peer-reviewed publications that scrutinized consumer behaviour, corporate practices, and their economic ramifications within the framework of international business, specifically those released between the years 2019 and 2025. 57 pertinent studies from a variety of databases were found during the review. A detailed compilation of observed facts reveals that investigations into promotional approaches, shopper habits, and governance models show a considerable variation. Significant notions involve a range of consumer patterns influenced by cultural diversity, the shift in business operations due to the digital revolution globally, and the strategies devised for consumer protection. Contemporary analyses indicate that important cultural dynamics significantly influence purchasing behaviours, in addition to noticeable differences in legal systems about consumer support. The current literature shows limited comprehensive economic analysis of consumer and commercial practices in international business. Understanding cross-cultural commercial practices and their economic ramifications, especially with regard to policy recommendations and economic impact assessments, is severely lacking